Resolution of Sterile Inflammation: Role for Vitamin C - Mohammed, Bassem M.; Fisher, Bernard J.; Huynh, Quoc K.; Wijesinghe, Dayanjan S.; Chalfant, Charles E.; Brophy, Donald F.; Fowler III, Alpha A.; Natarajan, Ramesh (Mediators of Inflammation, 2014)
Introduction. Macrophage reprogramming is vital for resolution of acute inflammation. Parenteral vitamin C (VitC) attenuates proinflammatory states in murine and human sepsis. However information about the mechanism by which VitC regulates resolution of inflammation is limited. Methods. To examine whether physiological levels of VitC modulate resolution of inflammation, we used transgenic mice lacking L-gulono-γ-lactone oxidase. VitC sufficient/deficient mice were subjected to a thioglycollate-elicited peritonitis model of sterile inflammation. Some VitC deficient mice received daily parenteral VitC (200 mg/kg) for 3 or 5 days following thioglycollate infusion. Peritoneal macrophages harvested on day 3 or day 5 were examined for intracellular VitC levels, pro- and anti-inflammatory protein and lipid mediators, mitochondrial function, and response to lipopolysaccharide (LPS). The THP-1 cell line was used to determine the modulatory activities of VitC in activated human macrophages. Results. VitC deficiency significantly delayed resolution of inflammation and generated an exaggerated proinflammatory response to in vitro LPS stimulation. VitC sufficiency and in vivo VitC supplementation restored macrophage phenotype and function in VitC deficient mice. VitC loading of THP-1 macrophages attenuated LPS-induced proinflammatory responses. Conclusion. VitC sufficiency favorably modulates macrophage function. In vivo or in vitro VitC supplementation restores macrophage phenotype and function leading to timely resolution of inflammation.